2020
DOI: 10.1186/s12877-020-01754-x
|View full text |Cite
|
Sign up to set email alerts
|

Negative stereotypes, fear and social distance: a systematic review of depictions of dementia in popular culture in the context of stigma

Abstract: Background Literature, film and news media reflect and shape social perceptions of dementia which in turn impact on dementia stigma. The aim of this paper is to systematically review papers on the depiction and frames for dementia in literature, film, mass media and social media in order to better understand cultural stigma related to dementia. Methods A systematic search of electronic databases was undertaken combining phrases relating to dementia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 85 publications
(187 reference statements)
1
74
0
Order By: Relevance
“…The responsibility for cognitive health and the blame for cognitive decline in old age might be shifted onto those who do not follow health and prevention recommendations and thus fail or refuse to live their lives in a healthy, active, and socially acceptable manner (Forlini & Hall, 2017). In interaction with degrading and objectifying images of dementia (Harvey & Brookes, 2019;Low & Purwaningrum, 2020), the strong emphasis on individual responsibility might support "victim-blaming of those living with dementia and result in increased stigmatization" (Lawless et al, 2018(Lawless et al, , p. 1548; see also Harris et al, 2016;Mohr et al, 2021;Peel, 2014). The responsibilization of cognitive aging could hence contribute to new forms of ageisms which replace the earlier general angst of aging with a specific fear of frailty, inability, and loss of cognitive abilities (Holstein & Minkler, 2003), and reinforce a devaluation of those who, due to physical and cognitive decline, can no longer comply with the ideal of self-reliant, successful aging.…”
Section: Stigmatizationmentioning
confidence: 99%
“…The responsibility for cognitive health and the blame for cognitive decline in old age might be shifted onto those who do not follow health and prevention recommendations and thus fail or refuse to live their lives in a healthy, active, and socially acceptable manner (Forlini & Hall, 2017). In interaction with degrading and objectifying images of dementia (Harvey & Brookes, 2019;Low & Purwaningrum, 2020), the strong emphasis on individual responsibility might support "victim-blaming of those living with dementia and result in increased stigmatization" (Lawless et al, 2018(Lawless et al, , p. 1548; see also Harris et al, 2016;Mohr et al, 2021;Peel, 2014). The responsibilization of cognitive aging could hence contribute to new forms of ageisms which replace the earlier general angst of aging with a specific fear of frailty, inability, and loss of cognitive abilities (Holstein & Minkler, 2003), and reinforce a devaluation of those who, due to physical and cognitive decline, can no longer comply with the ideal of self-reliant, successful aging.…”
Section: Stigmatizationmentioning
confidence: 99%
“…Some corresponding titles are: ‘I have to treat patients like objects: the harsh reality of working in dementia care’ (the GDN); ‘Living with the patients I’m losing to AD’ (the NYT). It can thus be further suggested that both newspapers are more likely to report on the care need or caregiving burden of dementia, which in turn impacts on the dementia-related social stigma [ 56 ]. Consequently, help-seeking behavior may be delayed, healthcare professionals may be reluctant to give a dementia diagnosis, and the overall human rights of people with dementia may be violated [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The depiction and prevalent contextualization of dementia in the news media is typically negative, which in turn impacts on public stigma, negative feelings, and social distance [ 55 , 56 ]. It further generates stereotypical images of PlwD that they are not fully human, are incompetent, and are burdens on society.…”
Section: Study Aim and Research Questionsmentioning
confidence: 99%
“…In the Middle East, a more spiritual and deterministic view of health and illness is used [ 13 , 14 ]. This attitude potentially contributes to stigmatization and reduces help-seeking behaviors [ 8 ]. Additional obstacles in studying dementia perceptions and engaging with dementia carers in the Middle East include language barriers, a lack of knowledge, lack of informal support outside of hospitals, and over-dependence on clinicians for dementia information [ 1 ].…”
Section: Barriers To Accessing Dementia Carementioning
confidence: 99%
“…A major problem faced by individuals living with dementia and their carers is stigmatization [7]. A stigma, or the process of stigmatization, refers to a sense of shaming or externally induced embarrassment regarding some characteristic [8]. Broad social and cultural shaming of mental health issues can reduce help-seeking behaviors and may cause embarrassment to adults with dementia, their families, and carers [4].…”
Section: Barriers To Accessing Dementia Carementioning
confidence: 99%